Vigilância das forças de segurança através de câmeras de reconhecimento facial e o conflito com o direito à privacidade - Carvalho, William Anderson Eloi de (2020)
This dissertation aims to analyze the conflict between the right to privacy and the use of face recognition cameras by security forces in Brazil and Portugal. The goal is to answer the following question: Does the right to privacy prevent the use of facial recognition technology in public safety? Before the answer is reached, the theme is contextualized, where the reality of both countries is verified, regarding public safety, and the gulf that separates Brazil from Portugal, where the former has homicide rates similar to those of countries at war, and the second is considered one of the safest countries in the world. Next, a study is done on Closed Circuit Television (CCTV) and facial recognition technology, showing how the system works and presenting data that prove its effectiveness. Then, legislation is analyzed from Brazil and Portugal to determine whether it is possible to employ CCTV systems with face recognition technology by the security forces, or whether this limits or prevents the exercise of rights and guarantees of citizens, focusing mainly on the right to privacy and the protection of personal data. Finally, the last chapter concludes the discussion, concluding that it is a conflict of fundamental rights, where current legislation harmonizes the coexistence of these rights, allowing the protection of fundamental rights and guarantees, while creating a scenario favorable to technological progress and the free movement of personal data. Thus, the answer to the original question is that, for Brazil and Portugal, the right to privacy does not prevent the use of facial recognition technology in public safety.